Integrasi Nilai Pancasila dalam Pembentukan Civic Disposition Melalui Pendidikan Pancasila: Systematic Literature Review - Syahwaliana, Kayla; Habib, Thifail Arrahmani; Shofiyah, Siti Nur Aina; Oki, Suprianto (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
This study aims to explore the integration of Pancasila values in the Pancasila Education curriculum as an effort to shape students' civic disposition in elementary schools. As the national ideology of Indonesia, Pancasila plays a crucial role in shaping national identity and serves as a moral and ethical guideline for all citizens. The background of this research focuses on the challenges of internalizing Pancasila values amid the influence of globalization, which affects the nation's character. The method used in this study is a literature review, employing the Systematic Literature Review (SLR) technique to analyze recent literature on character education based on Pancasila. Literature sources were obtained from journals available on Google Scholar. The results indicate that one of the most effective ways to integrate Pancasila values through civic disposition in Pancasila Education is by incorporating these values into every aspect of the learning process. Through habituation and role modeling, Pancasila’s noble values can be effectively instilled in students. Furthermore, effective teaching methods can enhance students’ understanding of their rights and responsibilities as citizens. In conclusion, integrating Pancasila values into the Pancasila Education curriculum is essential for building a strong and sustainable national character.